Preva Lence Of Quantitative And Qualitative Polypharmacy In Older Adults With Alzheimer Dementia - Patrícia Medeiros de Souza; Liana Tieko Evangelista Kusano; Leopoldo Luiz dos Santos Neto (Brazilian Society of Geriatrics and Gerontology, 2024)
BACKGROUND: Polypharmacy can be defined quantitatively or qualitatively. One of the concepts underlying the quantitative definition of polypharmacy is the use of two or more medications. The qualitative definition, in turn, takes into account the rationalization of pharmacotherapy. OBJECTIVES: Based on these two concepts, this study aimed to determine the prevalence of polypharmacy in older adults with dementia and correlate it with sociodemographic, clinical, and pharmacological characteristics. METHODS: A cross-sectional study was conducted in a center of excellence for dementia care in the Federal District, including 97 older adults with a diagnosis of Alzheimer dementia. Prevalence rates were determined for quantitative and qualitative polypharmacy. The presence of polypharmacy was correlated with the characteristics of the sample by univariate analysis. Descriptive statistics were calculated for all dependent and independent variables. The correlation between secondary variables and polypharmacy was determined by prevalence ratio. Univariate analysis was performed using the following statistical tests: Pearson's χ2 test, Kruskal-Wallis test, and Wilcoxon-Mann-Whitney (WMW) test. RESULTS: The prevalence of quantitative polypharmacy was 92.8%, of which 37.2% were characterized as minor, 25.8% as moderate, and 29.8% as major. The prevalence of qualitative polypharmacy was 49.5%. Sociodemographic and clinical characteristics were not associated with quantitative or qualitative polypharmacy. CONCLUSION: Both quantitative and qualitative polypharmacy were highly prevalent among older adults with dementia. The delivery of multidisciplinary care to older outpatients through a methodology that identifies and characterizes polypharmacy both quantitatively and qualitatively seems to be a useful tool to promote the rational use of medications.